2017
DOI: 10.1111/jav.01220
|View full text |Cite
|
Sign up to set email alerts
|

Wing size but not wing shape is related to migratory behavior in a soaring bird

Abstract: Both wing size and wing shape affect the flight abilities of birds. Intra and inter‐specific studies have revealed a pattern where high aspect ratio and low wing loading favour migratory behaviour. This, however, have not been studied in soaring migrants. We assessed the relationship between the wing size and shape and the characteristics of the migratory habits of the turkey vulture Cathartes aura, an obligate soaring migrant. We compared wing size and shape with migration strategy among three fully migratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…2 ). Therefore, we eliminate the possibility of misinterpreting an interrupted foraging response due to breeding (Nwaogu et al 2017 ), starvation risk (Macleod and Gosler 2006 ) or migration (Hahn et al 2015 ; Grilli et al 2017 ) as conforming to Bergmann’s rule. Unfortunately, both wing length and body mass have been used on their own to test Bergmann’s rule (Watt et al 2010 ) and this may lead to misleading interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Therefore, we eliminate the possibility of misinterpreting an interrupted foraging response due to breeding (Nwaogu et al 2017 ), starvation risk (Macleod and Gosler 2006 ) or migration (Hahn et al 2015 ; Grilli et al 2017 ) as conforming to Bergmann’s rule. Unfortunately, both wing length and body mass have been used on their own to test Bergmann’s rule (Watt et al 2010 ) and this may lead to misleading interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the heart rate of the studied bird only slightly increased with distance traveled, demonstrating the highly efficient flight performance of this long-distance migrating species. Similarly, a recent study also found that migrating Turkey Vultures showed differences in a set of movement-related metrics (i.e., distance, duration, speed and altitude of migration) as a result of differences in wing loading, which suggests that wing morphology could influence the selection of migration routes [ 71 ]. Among the internal mechanistic components that shape vulture migration, navigation capacity remains largely unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…Wing morphology has increased importance for species relationships with the environment because they dictate the type of flight, the energetics of flight performance, the life‐history strategies and the ecological patterns such as habitat use and foraging strategies in several spatial scales (Norberg & Rayner, 1987; Marinello & Bernard, 2014; Grilli et al ., 2017; Sullivan, Meyers & Arzt, 2019). For bats, RWL and AR influence ecological dynamics, from local to broad geographical scales, exemplified by their impacts on habitat, resource use and biogeography (Norberg & Rayner, 1987; Marinello & Bernard, 2014; Luo et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%